A clinical study on risk- factors and feto-maternal outcome of pre-eclampsia in Bangladesh - Khan, Shaila; Aleem, Natasha Tiluttoma; Ul Hasna, Asma; Husein, Sabina; Khatun, Kashefa; Ara, Raushan (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Preeclampsia (PE) is a major cause of maternal and foetal mortality and morbidity. Aim The purpose of the present study was to identify the risk factors, prognosis, maternal and foetal outcome of pre eclampsia patients. Methods This descriptive type of cross sectional hospital based study was conducted in the Department of Obstetrics & Gynecology at Bangabandhu Sheikh Mujib Medical University (BSMMU) & Dhaka Medical College Hospital (DMCH), Dhaka for a period of 6 months. All admitted cases of pre-eclampsia patients who were given the consent were included in the study. Then a thorough history was taken followed by relevant clinical examination and some base line investigation done. For renal function urine for protein, blood for urea, creatinine and uric acid estimation were done. All the information were recorded in a predesigned data collection sheet. Fetal monitoring was done by observing foetal movement, foetal heart sound 6 hourly, ultrasonography of lower abdomen to see foetal well-being and amniotic fluid volume. Maternal and fetal complications were monitored. Results The incidence of preeclampsia was found in 3.4% in this study. Among the studied patients highest percentage had complaints of swelling of legs and abdominal pain (38%). In this study 46% pregnancies were terminated in 29-34 weeks of gestation. Obstetric examination revealed that 42% fundal height 29-34 weeks. Among the study population 4% patients developed abruptio placenta, 2% patients developed post partum eclampsia and 2% patients developed disseminated intravascular coagulation. In the developing countries the perinatal mortality in pre-eclampsia remains to the extent of about 20%, about 50% of which is being still born. In this study 80%, pregnancies gave live born foetus, 6% pregnancies still born babies and Intra uterine death occurred in 6% pregnancies, 8% pregnancies ended in abortion, before the age of viability of foetus. In the study population intrauterine growth retardation was present in 50% babies, 52% babies were premature, still birth was 6%, Intra uterine death was in 6% cases, and abortion was 6%. The IUGR babies also were premature. In this study 28% pregnancies had no foetal or maternal complication. Only foetal complication was present in 60% pregnancies. Only maternal complication was present in 2% pregnancies. Both maternal and foetal complication was present in 10% pregnancies. Conclusion In this study concluded that the abruptio placenta, post partum eclampsia and DIC are common complications of pre-eclampsia patients. Perinatal mortality and still born are also found though live born foetus are the most common. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19815 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 39-44